Spring temperatures affect senescence and N uptake in autumn and N storage for winter in Rhynchospora alba (Cyperaceae). (12th November 2019) - Byne, Kyelle; Ryser, Peter
Abstract : Autumn senescence is delayed and nitrogen uptake extended in response to a late onset of spring, but the resulting inefficiency of remobilization reduces the amount of nutrients stored for winter. Abstract: Environmental and physiological factors underlying variation in timing of autumn senescence are not well known. We investigated how the time of the onset of the growth in spring affects senescence and its functional consequences for nitrogen (N) uptake in autumn and storage of N for the winter, in a species that each year develops its bulbils for storage and overwintering anew. Rhynchospora alba was grown outdoors with two treatments, identical except for a 3 week difference in the start of growth in May. Leaf and root growth and senescence, and N uptake were recorded from August to November. By August, late-starting plants had caught up in size and total N content, but had smaller bulbils. They had a higher δ  13 C, indicating a higher stomatal conductance during growth. Leaf and root senescence were delayed, extending 15 N tracer uptake by 4 weeks. Nevertheless, after senescence, plants with an early start had 55% more N in their overwintering bulbils, due to earlier and more efficient remobilization. We conclude that timing of senescence in R. alba is a result of an interplay between the status of winter storage and cold temperatures, constrained by a trade-off between prolonged nutrient uptake and efficient remobilization of nutrients.